Designing Educational Games with Mastery Learning Strategy to Improve Computational Thinking Skills: A Bibliometric Analysis - Emilia Candrawati; Ijang Rohman; Ratnaningsih Eko Sardjono; Binar Kurnia Prahani; Satwika Trianti Ngandoh (UIN Fatmawati Sukarno Bengkulu, 2025)
Students need computational thinking skills to help them face global challenges with rapid technological development. For this reason, teachers must be able to implement CT in learning by paying attention to students' interest in learning, one of which is using educational games. Designing CT-integrated educational games requires appropriate strategies such as mastery learning. This study aims to analyse the development of educational game design using mastery learning strategies so that it can provide an overview to educators in developing the media to improve students' CT skills. This research uses a qualitative descriptive method. The data obtained was analysed bibliometrically using the VOS Viewer application. The VOS Viewer analysis shows that there is a connection between game design, computational thinking, and mastery learning that began in 2016. The results also show that there are 4 things that become the basis for designing educational games, namely cognitive, motivational, affective, and sociocultural perspectives